2010
DOI: 10.1111/j.1574-6941.2010.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrifiers and denitrifiers respond rapidly to changed moisture and increasing temperature in a pristine forest soil

Abstract: Complete cycling of mineral nitrogen (N) in soil requires the interplay of microorganisms performing nitrification and denitrification, whose activity is increasingly affected by extreme rainfall or heat brought about by climate change. In a pristine forest soil, a gradual increase in soil temperature from 5 to 25 degrees C in a range of water contents stimulated N turnover rates, and N gas emissions were determined by the soil water-filled pore space (WFPS). NO and N(2)O emissions dominated at 30% WFPS and 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
118
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(142 citation statements)
references
References 50 publications
(59 reference statements)
20
118
2
2
Order By: Relevance
“…The total abundance of N cycle genes has been shown to respond to increased temperature (Szukics et al, 2010). Consistently, we found an increase in the relative abundance of microbial N cycle genes at the NS site, and to a lesser extent at the NC site (Figure 1).…”
Section: Resultssupporting
confidence: 73%
“…The total abundance of N cycle genes has been shown to respond to increased temperature (Szukics et al, 2010). Consistently, we found an increase in the relative abundance of microbial N cycle genes at the NS site, and to a lesser extent at the NC site (Figure 1).…”
Section: Resultssupporting
confidence: 73%
“…Our results show that soil warming did not significantly change the amoA gene copy numbers of AOA (see Fig. 1b), which is consistent with the result from an elevated temperature experiment in a pristine forest soil (Szukics et al 2010) and that the amoA gene copy numbers of AOB decreased significantly with fertilization (i.e., HF<F, Fig. 1b).…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertisupporting
confidence: 79%
“…Ebrahimi et al [21] found that, in two sequencing batch reactors (SBR) operated at 20ºC, 30ºC, and 35ºC, bacterial richness and diversity were clearly altered. Several other studies also demonstrated that temperature imposed a strong selective pressure on bacterial communities of activated sludge [22][23][24][25]. As with temperature, DO was also strongly and significantly linked to bacterial community variance in CCA analyses.…”
Section: Relationship Of Environmental Factors To the Bacterial Commumentioning
confidence: 63%